2017
DOI: 10.18632/oncotarget.20731
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus in tumor-infiltrating B cells of myasthenia gravis thymoma: an innocent bystander or an autoimmunity mediator?

Abstract: The thymus plays a key role in myasthenia gravis (MG), a B cell-mediated autoimmune disorder affecting neuromuscular junction. Most MG patients have thymic abnormalities, including hyperplasia and thymoma, a neoplasm of thymic epithelial cells. Epstein-Barr virus (EBV) is associated with autoimmune diseases and tumors. Recently, we showed EBV persistence and reactivation in hyperplastic MG thymuses, suggesting that EBV might contribute to intra-thymic B cell dysregulation in MG patients. Here, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 60 publications
4
43
0
Order By: Relevance
“…Taken together, our data clearly indicate that latently infected B cells are present in the thymus. This principal finding is in accordance with recent reports suggesting that EBV can reside in thymic B cells and express an unusual combination of viral genes ( and references cited therein), which is, however, a controversial finding . What remains to be shown is whether infected B cells in the thymus express viral genes that can result in a functional T‐cell tolerance against certain viral epitopes.…”
supporting
confidence: 90%
“…Taken together, our data clearly indicate that latently infected B cells are present in the thymus. This principal finding is in accordance with recent reports suggesting that EBV can reside in thymic B cells and express an unusual combination of viral genes ( and references cited therein), which is, however, a controversial finding . What remains to be shown is whether infected B cells in the thymus express viral genes that can result in a functional T‐cell tolerance against certain viral epitopes.…”
supporting
confidence: 90%
“…In contrast to healthy individuals, MG patients have hyperplastic and involuted thymuses infiltrated with EBV B- and plasma cells. This suggests that the virus could be implicated in the autoimmune process within intra-thymic MG, possibly by the activation and perpetuation of autoreactive B cells and the stimulation of pathogenic TLR7 and TLR9 signaling [ 124 ]. In a study done in Japan, researchers found that antibodies against EBV early antigen IgG (anti-EA) was significantly elevated in the serum of NMO patients in comparison to MS patients and controls.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…31,35 We found that transcriptional levels of both TLR7 and TLR9 were significantly higher in each MG thymus subgroup than in the control thymus group (relative expression values: 5.2 ± 0.8 versus 0.62 ± 0.08 for TLR7, P < 0.01; 1.05 ± 0.2 versus 0.21 ± 0.11 for TLR9, P < 0.05), without any effect of prethymectomy treatment with corticosteroids on thymic TLR7 and TLR9 expression. 23 By contrast, expression of the two receptors was not significantly altered in thymomas from MG patients compared with thymomas from patients without MG and normal thymuses, 59,60 suggesting that intrathymic TLR7 and TLR9 overexpression is a prominent feature of nonthymomatous MG. Intriguingly, we observed a strong overexpression of TLR7 and TLR9 in B cells and plasma cells of hyperplastic and involuted MG thymuses in comparison with B cells and plasma cells of control thymuses (Fig. 1).…”
Section: Tlr7 and Tlr9 Contribution To B Cell Dysfunction And Autoimmmentioning
confidence: 98%